RANCANGAN ALAT PENGHANCUR SAMPAH PADA GREASE TRAP UNTUK SISTEM SANITASI DI BANDAR UDARA INTERN - Harman Sudjanto; KGS. M. Ismail; Haret Rahma Fitri (Politeknik Penerbangan Indonesia Curug, 2016)
Recently, Kualanamu International Airport – Medan has 12 units grease trap. The function of grease trap is filtering the fat which is produced by stainless and filtering the oil, fat and rubbish fom the toilet and restaurant in the terminal of the airport. So far, in order to filter the rubbish, garbage and fat from grease trap in the terminal is using manual technique. The technician hires contractor to move the garbage, rubbish and fat by using bucket into pick-up car then throws into Sump Pit. If they ignore all of this steps, it can cause bad smell around the airport.